Can icons enhance requirements engineering work?. (June 2015) - Khanom, Sukanya; Heimbürger, Anneli; Kärkkäinen, Tommi
Abstract: When novel artifacts are proposed, their usability must be taken into account. We argue that effective visual notation depends critically on its usability, which assists members in more easily communicating with each other while reducing misunderstanding. In this paper, we extend prior research by elaborating already-refined artifacts (requirements engineering modeling, icon-based modeling and user preference modeling), and by carrying out summative (confirmatory) evaluation. The summative evaluation assists in determining artifacts׳ utility. Employing usability measurements, we examine perceptive, ergonomic, and hedonic qualities. The tests were performed in three series of iterations by two groups of practitioners. The first iteration was assigned to a few selected experts in computer and software companies to execute pre-testing. The second iteration was tested by the rest of the experts in the computer and software companies. The third iteration was examined by PhD students in the Faculty of Information Technology at the University of Jyväskylä. The findings demonstrate the usability of an icon-based approach, integrating altogether three artifacts, that serves users in a novel yet fairly effective manner. We suggest that an icon-based approach could serve as a positive basis on which to construct a requirements engineering visual notation that is easily understood and learned. Abstract : Highlights: Introducing a novel visual notation to enrich requirements engineering work. Drawing upon design science research to construct-and-evaluate artifacts. Developing demonstrator through MediaWiki. Presenting confirmatory evaluations by experts and PhDs.